Transformasi Ekonomi Desa Melalui Edukasi dan Implementasi Label Produk Halal - Zaenol Hasan; Ahmad Faqihuddin; Ahmad Sovil; Khaerul Anam (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Rural economic transformation is a strategic step in improving the welfare of rural communities, especially in the era of globalization that drives intense market competition. One important aspect of this transformation is education and the implementation of halal production labeling. The application of halal labels not only increases consumer trust but also opens up opportunities for local products to be exported to global markets that increasingly emphasize product halalness. Education about the importance of halal certification at the village level becomes crucial in enhancing the quality and competitiveness of local products. Moreover, empowering communities through training and mentoring in the halal certification process can accelerate economic transformation. This research aims to analyze the impact of education and the implementation of halal certification on rural economic growth and identify the challenges faced in the process. The findings reveal that villages that have implemented halal certification experienced increased income, wider market access, and improved product quality. However, obstacles such as a lack of knowledge and high certification costs need to be addressed through more inclusive policies and government support.